Empowering Peer Counselors Through the Pik-R Program to Prevent Early Marriage Among Middle School Adolescents In Bima District - Kurniadi,; A. Haris,; Sukmawati Sukmawati,; Supriadin Supriadin, (International Journal of Scientific Research and Management (IJSRM), 2023)
An estimated three million girls aged 15–19 years have unsafe abortions every year and complications from pregnancy and childbirth are the leading cause of death among pregnant teenagers. Objectiveempowering peer counselors through the pik-r program to prevent early marriage among middle school teenagers in Bima district. This type of research is analytical research, the research method used in this research is a quasi experiment with a pre test and post test with control group design. The sample in this study was high school students in Woha District, Bima Regency and was in accordance with research criteria. The number of samples in this study was calculated using the sample size formula according to Slovin. The total sample in this study was 172 with a division of n1: 86 respondents and n2: 86 respondents. The tool used to measure the level of knowledge is in the form of a questionnaire to determine teenagers' knowledge and attitudes about reproductive health to prevent early marriage. Bivariate tests were carried out to determine the influence and differences in levels of knowledge and attitudes in the control group and treatment group. This research uses the Paired T-Test statistical test or the alternative Wilcoxon Signed Rank test. The study found that both intervention and control groups showed improved knowledge and skills through PIK-R training, with the intervention group showing more positive responses and the control group showing more negative responses, suggesting a potential improvement.